PRAKTEK UPAH MENGUPAH BASIANG PADI DENGAN SISTEM INDAK DILAPESI DALAM TINJAUAN FIQIH MUAMALAH - Vioni Afya Ningsih; Yustiloviani Yustiloviani (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the review of muamalah fiqh on the practice of paying basiang padi with the indak dilpaesi system in Jorong Balimbing. The purpose of this study was to identify and explain the practice of paying basiang padi with an uncoated system, as well as to explain a review of muamalah fiqh on the practice of paying basiang padi with an uncoated system in Jorong Balimbing, Nagari Balimbing. The research method used is a qualitative research method by conducting field research with observation and interview data collection techniques. The research finding is that the wage practice of paying basiang padi with the indak dilapesi system in Jorong Balimbing is done by paying part of the agreed wage, which is given wages to cultivators as much as 4 liters of rice while wages should be paid 6 liters of rice. Based on the principle of fairness, wages for basiang padi with the indak dilapesi system are not in accordance with the pillars and conditions of wages. There is an element of injustice in delaying the payment of wages and reducing the payment of wages to the detriment of one party, this is not allowed in muamalah fiqh.